PRODUCT MODIFICATION TRAINING AND DIGITAL MARKETING IN THE PANDEMIC ERA: MSMES PRODUCTION EMPING PANCUR VILLAGE, SERANG CITY - Maelani, Puspita; Rois, Khafidz; Fahira, Fawza (Ekalaya: Jurnal Pengabdian Kepada Masyarakat Indonesia, 2024)
MSMEs are trading businesses carried out by individuals or groups that refer to productive economic businesses. The business carried out by individuals or groups in Sepring, Pancur Village, Taktakan, is a processed business from melinjo, namely emping. Conventional marketing, namely by marketing directly to local markets or areas, products that are still original chips, and the Covid-19 pandemic are obstacles for MSMEs. This training method has stages, the first stage is a direct survey to see the production and marketing process of MSMEs, the second stage is planning and implementation. The result of this training activity is that it can increase the knowledge of MSME business actors about the legality and licensing of institutions or products, knowledge about modifying products according to market needs and implementing digital marketing through a marketplace or online shop in collaboration with village youths..